Magnetic resonance-based pelvimetry and tumor volumetry can predict surgical difficulty and oncologic outcome in locally advanced mid-low rectal cancer - Atasoy, Gülşen; Arslan, Naciye Çiğdem; Dinç Elibol, Funda; Sa?ol, Özgül; Obuz, Funda; Sökmen, Selman (Springer Tokyo, 2018)
PurposeTo investigate the impact of the pelvic dimensions and tumor volume on surgery in locally advanced rectal cancer.MethodsPatients who underwent open surgery after neoadjuvant long-course chemoradiation for primary rectal cancer were included. The predictive value of magnetic resonance-based pelvic measurements and tumor volume on the surgical difficulty and oncologic outcome were analyzed.Results125 patients were included. The independent risk factors related to the circumferential resection margin status were the pT stage [odds ratio (OR) 3.64, confidence interval (CI) 1.409-7.327] and tumor volume after neoadjuvant chemoradiotherapy (OR 1.59, CI 1.018-2.767). The operative time (p=0.014, OR 1.453) and pelvic depth (p=0.023, OR 1.116) were independent predictive factors for anastomotic leak. The median follow-up was 72 (2-113) months. Local recurrence was seen in 17 (14.1%) patients. Anastomotic leak (OR 1.799, CI 0.978-3.277), the circumferential resection margin status (OR 3.217, CI 1.262-7.870) and the relative tumor volume rate (OR 1.260, CI 1.004-1.912) were independent prognosticators of local recurrence. The 5-year overall survival was 66.7%. The circumferential resection margin status (hazard ratio: 4.739, CI 2.276-9.317), pN stage (OR 3.267, CI 1.195-8.930) and relative tumor volume rate (OR 2.628, CI 1.042-6.631) were independent prognostic factors for the overall survival.ConclusionsRelative dimensions of the tumor in the pelvis influence the local recurrence and overall survival rates. Magnetic resonance-based measurements can predict the difficulty of surgery and allow surgeons to consider the appropriate surgical approach.
WOS: 000447980700002
PubMed ID: 29961173
Keywords: Pelvimetry; Magnetic Resonance; Rectal Cancer; Survival; Local Recurrence